Impact of Herbicidal Weed Management on Weed Flora, Productivity, and Soil Microbial Population in Groundnut (Arachis hypogaea L.) and its Residual Effect on Lathyrus (Lathyrus sativus L.) - Jana, Kalyan; Nesha, Munmun; Sarkar, Arup; Pramanik, Antara; Mondal, Ramyajit; Verma, Nidhi; Banerjee, Subhajit (International Journal of Bio-resource and Stress Management, 2026)
The experiment was conducted during the months of July-February of 2022–23 and 2023–24 at the Instructional Farm, Bidhan Chandra Krishi Viswavidyalaya, Mohanpur, Nadia, West Bengal, India to study the best weed management practice in groundnut crop (kharif season) and its residual effect on succeeding lathyrus crop (rabi season). The study had seven treatments replicated thrice namely; T1: Fluazifop-p-butyl 13.4% EC @ 1000 ml ha-1; T2: Fluazifop-p-butyl 13.4% EC @ 1250 ml ha-1; T3: Fluazifop-p-butyl 13.4% EC @1562.5 ml ha-1, T4: Quizalofop ethyl 5% EC@1000 ml ha-1, T5: Fluazifop-p-butyl 13.4% EC @ 2500 ml ha-1, T6: Hand weeding control (20 and 40 days after sowing), T7: Weedy check control. The results revealed that Fluazifop-p-butyl 13.4% EC @ 2500 ml ha-1 provided effective control of all weed categories but caused severe phytotoxicity, resulting in marked yield reduction in groundnut. The twice hand weeding at 20 and 40 DAS recorded the highest weed control efficiency and maximum groundnut yield; however, its higher labour cost led to a comparatively lower benefit-cost ratio. However, among the herbicidal treatments, Fluazifop-p-butyl 13.4% EC @ 1562.5 ml ha-1 produced the best overall performance with effective weed suppression, higher pod, kernel, and haulm yields, and the maximum benefit-cost ratio. The germination, yield, and yield-attributing traits of the succeeding lathyrus crop were not significantly influenced by the preceding herbicidal treatments. Hence, Fluazifop-p-butyl 13.4% EC @ 1562.5 ml ha-1 might be safely recommended for effective weed management in groundnut in the lower Gangetic alluvial zone of West Bengal.